From policy to practice: Examining the role of recess in elementary school - Janelle Thalken; William V. Massey; Alexandra Szarabajko; Isabella Ozenbaugh; Laura Neilson (Elsevier, 2021)
Objectives: To examine the relationship between school recess policies, the quality of the recess environment and body mass index (BMI) among elementary school children. Study design: Observational. Methods: Data were collected at 23 schools across four geographically distinct regions of the United States. Measures included recess observations using the Great Recess Framework-Observational Tool (GRF-OT), recess policies were collected with the School Physical Activity and Policy Assessment, and BMI was obtained through height and weight measurements among 429 students in third and fifth grade. Results: Results showed that school policies related to recess access significantly predicted children's BMI, and school policies related to investment in recess significantly predicted recess quality as measured by the GRF-OT. Conclusions: Results from this study can be used to help inform future research regarding how school recess policies can impact child-level outcomes and the recess environment.